Community Empowerment Training Through Local Potential - Sugiyarmasto Sugiyarmasto; Herman Mawengkang (International Journal of Community Service Implementation, 2023)
University as an academic institution has a massive potential to built-in entrepreneurs with extensive concept. This have been formed by Setia Budi University with funding the Community Service Programmed which aimed to increase the quality of community in economic, academic and prosperity. Based on that program, the community serviced program about training of making Souvenir will be held in Tambora Tengah , Kelurahan Mojosongo, KecamatanJebres where placed in Setia Budi University area. This district has 21;RW, and 04 RT which has about 30 families each.According to that situation, come up the idea to help each family to be more productive and earning trough training. This training of making souvenir amimed to increase the productivity and passive income to develop and self-supporting the family prosperity.This entrepreneurship in developing souvenir business identic as woman business activity which has time and energy effective and not disturbing their activity and responsibility as a housewife.